2022
DOI: 10.1097/aco.0000000000001133
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric and perinatal racial and ethnic disparities

Abstract: Purpose of reviewHealthcare disparities are health differences that adversely affect disadvantaged populations. In the United States, research shows that women of color, in particular Black and Hispanic women and their offspring, experience disproportionately higher mortality, severe maternal morbidity, and neonatal morbidity and mortality. This review highlights recent population health sciences and comparative effectiveness research that discuss racial and ethnic disparities in maternal and perinatal outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…144,145 These factors make it more difficult for them to get access to reproductive health resources. Even after controlling for socioeconomic factors such as education, income, or access to health care, racial and ethnic disparities have been reported for unintended pregnancies, 146,147 cervical cancer, sexually transmitted infection screening, 148,149 mental health care, 150 and obstetric and perinatal care, 151,152 and for women's ability to obtain accurate information related to general health and reproductive health on the internet. 153 A Veteran Affairs Health System's study of veteran women found that racial and ethnic disparities also extend to knowledge about contraceptives.…”
Section: Racial and Ethnic Disparitiesmentioning
confidence: 99%
“…144,145 These factors make it more difficult for them to get access to reproductive health resources. Even after controlling for socioeconomic factors such as education, income, or access to health care, racial and ethnic disparities have been reported for unintended pregnancies, 146,147 cervical cancer, sexually transmitted infection screening, 148,149 mental health care, 150 and obstetric and perinatal care, 151,152 and for women's ability to obtain accurate information related to general health and reproductive health on the internet. 153 A Veteran Affairs Health System's study of veteran women found that racial and ethnic disparities also extend to knowledge about contraceptives.…”
Section: Racial and Ethnic Disparitiesmentioning
confidence: 99%
“…4–8 Intraoperative anesthesia healthcare disparities have not been thoroughly investigated, and the precise contribution of anesthesiologists to these disparities is questionable; disparities identified in anesthesia procedure times, blood transfusion use, and neuraxial or regional anesthesia use cannot be conclusively attributed to the anesthesiologist’s practice patterns because patient, surgeon, and institutional preferences confound medical decision-making. 5,8–18 For instance, while previous research has found racial differences in anesthesia procedure times, these findings were attributed to interhospital and surgical duration differences. 9,10…”
mentioning
confidence: 99%
“…[4][5][6][7][8] Intraoperative anesthesia healthcare disparities have not been thoroughly investigated, and the precise contribution of anesthesiologists to these disparities is questionable; disparities identified in anesthesia procedure times, blood transfusion use, and neuraxial or regional anesthesia use cannot be conclusively attributed to the anesthesiologist's practice patterns because patient, surgeon, and institutional preferences confound medical decision-making. 5,[8][9][10][11][12][13][14][15][16][17][18] For instance, while previous research has found racial differences in anesthesia procedure times, these findings were attributed to interhospital and surgical duration differences. 9,10 We previously demonstrated antiemetic administration disparities for postoperative nausea and vomiting by socioeconomic status with differences in administration by insurance status (Medicaid vs. commercially insured patients receiving less antiemetic) and by median income in patient ZIP code (lower vs. higher median income patients receiving less antiemetics).…”
mentioning
confidence: 99%